Spatial and social determinants of transportation and recreational physical activity among adults in Hatyai City, Songkhla, Thailan - Saowaphan Churangsarit (Prince of Songkla University, 2021)
Thesis (M.Sc., Epidemiology)--Prince of Songkla University, 2009